Book Reviews. Issue 1 (1st March 2015) - West, Rebecca; O'Donnell, Hugh; Renga, Dana; O'Leary, Alan; O'Rawe, Catherine; Maio, Barbara; Hipkins, Danielle; Orton, Marie; Bayman, Louis; Di Lullo, Mauro
The Italian Cinema Book, Peter Bondanella (ed.) (2014) London: British Film Institute (Palgrave Macmillan), 380 pp., ISBN: 9781844574049, p/bk, £25.99Il prisma dei generi. Immagini DI donne in tv, Milly Buonanno (ed.) (2014) Milan: FrancoAngeli, 220 pp., ISBN: 9788891706041, p/bk, €29.00Reframing Italy: New Trends in Italian Women's Filmmaking, Bernadette Luciano and Susanna Scarparo (2013) West Lafayette, Indiana: Purdue University Press, 245 pp., ISBN: 978I557536556, p/bk, $45.00Da Ercole a Fantozzi: Cinema Popolare e Società Italiana dal Boom Economico alla Neotelevisione (1958–1976), Giacomo Manzoli (2012) Rome: Carocci, 254 pp., ISBN: 9788843048632, p/bk, €25Migrant Memories: Cultural History, Cinema and the Italian Post-War Diaspora in Britain, Margherita Sprio (2013) Oxford: Peter Lang, 290 pp., ISBN: 3034309473, p/bk, £45.Tempo di Fiction. Il racconto televisivo in divenire, Milly Buonanno (ed.) (2013) Napoli: Liguori Editore, 168 pp., ISBN: 9788820761295, p/bk, €16.99Italian Women Filmmakers and the Gendered Screen, Maristella Cantini (ed.) (2013) New York: Palgrave, 284 pp., ISBN: 9781137336507, h/bk (also available as an ebook), $95The Cinemas of Italian Migration: European and Transatlantic Narratives, Sabine Schrader and Daniel Winkler (eds) (2013) Cambridge: Cambridge Scholars Publishing, 326 pp., ISBN: 9781443846240, h/bk, $85.00Il cinema specchio della realtà. Modelli culturali a confronto, Francesca Borrione (2013) Rome: Aracne, 108 pp., ISBN: 9788854855663, p/bk, €11La Glocalizzazione digitale dell'audiovisivo. Nuovi Paradigmi nel Panorama Mondiale, Paolo Sigismondi (2014) Milan: Franco Angeli, 203 pp., ISBN: 9788820458324, p/bk, €22.50